2023
DOI: 10.3389/fpsyg.2023.1157409
|View full text |Cite
|
Sign up to set email alerts
|

Are happier adolescents more willing to protect the environment? Empirical evidence from Programme for International Student Assessment 2018

Abstract: A large number of existing studies have discussed the potential factors affecting pro-environmental behaviors (PEBs) in adolescents. However, few studies have focused on the possible impact of adolescents’ subjective wellbeing (SWB) on their PEBs. Why and how adolescents’ SWB affects their PEBs remains a puzzle. To unravel this puzzle, this paper aims to establish a suitable instrumental variable (IV) to correctly estimate the contribution of adolescents’ SWB to their PEBs. Using the international data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 108 publications
0
0
0
Order By: Relevance
“…For age or grade, results are also likely to reveal a nonsignificant association with PEB [48,59,74,76,79]. When significant, results reveal that being older was both positively [36,47,68,85,86] and negatively [12,56,57,69] associated with PEB. For adolescents' ethnicity, results reveal a nonsignificant relationship with PEB [51,58,60,76,77,79], except for Krettenauer et al [57] who found that Chinese adolescents reported more PEB than Canadian adolescents.…”
Section: Individual Correlatesmentioning
confidence: 94%
See 1 more Smart Citation
“…For age or grade, results are also likely to reveal a nonsignificant association with PEB [48,59,74,76,79]. When significant, results reveal that being older was both positively [36,47,68,85,86] and negatively [12,56,57,69] associated with PEB. For adolescents' ethnicity, results reveal a nonsignificant relationship with PEB [51,58,60,76,77,79], except for Krettenauer et al [57] who found that Chinese adolescents reported more PEB than Canadian adolescents.…”
Section: Individual Correlatesmentioning
confidence: 94%
“…First, multiple studies have looked at sociodemographic factors as correlates of PEB or control variables, including gender, age, ethnicity, living in a rural versus an urban location, parents' education, and family income. For gender, studies suggest either that there is no significant relationship between gender and PEB [9,12,47,51,58,59,73,74,76,77,79], that females engage in more PEB than males [36,49,63,68,69] or that males engage in more PEB than females [60,85,86,88]. For age or grade, results are also likely to reveal a nonsignificant association with PEB [48,59,74,76,79].…”
Section: Individual Correlatesmentioning
confidence: 97%
“…It was an essential concern for psychologists like Dewey, Mead, and Barker. (6) The ecological theory by Brofenbrenner suggests that we co-exist with our environments and that our behavior exists because of our environment. (7,8) Environmental hazards like air pollution and bad weather are associated with poor mental health outcomes, such as depression and anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%